Strengthening health systems resilience using environmental surveillance for COVID-19 and antimicrobial resistance in the Philippines - Salazar, Miguel Antonio; Dalmacio, Leslie Michelle M; Orbecido, Aileen H; Abanador, Ruth C; Promentilla, Michael Angelo; Beltran, Arnel B; Tanhueco, Renan Ma T; Balolong, Marilen Parungao (Western Pacific Surveillance and Response, 2022)
COVID-19 has turned into a protracted emergency to Philippine urban populations. The pandemic can be an opportunity for the country to strengthen surveillance capacity through wastewater-based epidemiology for COVID-19 and antimicrobial resistance. This capacity can translate to detection and monitoring for other emerging infectious diseases.